2008
DOI: 10.1620/tjem.216.353
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Prehypertension Is Associated with the Increased Body Mass Index in Community-Dwelling Japanese

Abstract: Hypertension and obesity are likely the most common disease in Japan. It has been reported that subjects with prehypertension (systolic blood pressure [SBP] 120-139 mmHg and/ or diastolic blood pressure [DBP] 80-89 mmHg) have also an increased risk of cardiovascular disease; however, only limited data are available on the prevalence of prehypertension and its association with body weight. We performed a cross-sectional study to examine whether the status of body weight was associated with prehypertension. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
5
12
0
1
Order By: Relevance
“…Regression analysis revealed that overweight/obesity was a significant predictor of prehypertension in our study. Similar findings were reported by several other studies [6,14,17,18,22,23]. The association between BP and weight is strong and linear, even in the normal range of BP and BMI [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regression analysis revealed that overweight/obesity was a significant predictor of prehypertension in our study. Similar findings were reported by several other studies [6,14,17,18,22,23]. The association between BP and weight is strong and linear, even in the normal range of BP and BMI [24].…”
Section: Discussionsupporting
confidence: 90%
“…Prehypertension was recognized to be more common among males than females, regardless of age [15][16][17][18]. Also, national studies conducted in Saudi Arabia revealed that hypertension was more common among males than females [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…14 However, the prevalence of prehypertension in 2002 in our study was higher than that (from 23.9 to 44.3%) in other studies conducted in China, Israel, the United States and Japan. [21][22][23][24] Although variations in geography, race, age and lifestyle in different studies may partially account for the differences in observed results, 12,24 the rapid increase in the prevalence of prehypertension from 1991 to 2002 in our study may be related to the more stressful workload, high-calorie and salty food, reduced physical activity and more common overweight and obesity in the rural area during the past two decades. 25,26 Although the term prehypertension is still in dispute, recent studies have found a positive correlation between prehypertension and major cardiovascular diseases in the Chinese population, 14,15 indicating that detection of prehypertension may have important clinical significance.…”
Section: Evolution Of Hypertension In China J Yang Et Almentioning
confidence: 67%
“…19,27,29,30,36,37 Pang et al 35 specifically found associations between BMI and elevated blood pressure. We found that overweight and obese subjects were more likely to develop prehypertension and hypertension, since overweight and obesity were more prevalent in prehypertensive and hypertensive than in normotensive groups.…”
Section: Bmimentioning
confidence: 99%